Advocacy for the adoption of arbitration for the resolution of commercial disputes in Nigeria (2020)
This paper advocates the adoption of arbitration for the resolution of commercial disputes in Nigeria. The two burning questions which the paper interrogates are: What is the legal framework for the resolution of commercial disputes in Nigeria? And to what extent has this legal framework meets the resolution of commercial dispute? To answer these questions, this paper adopts doctrinal methodology in legal research and relied heavily on desktop search for information. The paper finds that advancement in commercial transactions the world over has largely been positively impacted by globalisation, liberalisation of markets, bilateral and multilateral agreements leading to the opening of more windows for commercial interactions at local and international space and therefore rendering the traditional court litigation process for resolution of commercial transactions ineffective. The paper observes that the shortcomings inherent in judicial process call for radical paradigm shift to arbitration as viable alternative to litigation in the resolution of commercial dispute. The paper concludes with recommendation among other for the adoption of arbitration as a major method for settlement of commercial dispute in Nigeria as antidote to the shortcomings in court litigation.